Health & Nutrition in Egypt: Egypt’s Performance & Way Forward - El-Enbaby, Hoda (2019)
As part of the IFPRI Egypt Seminar in partnership with the National Nutrition Committee (ASRT affiliated): "100 million healthy lives: Scientific evidence on the double burden of malnutrition in Egypt"